Key stage 3 geographical enquiry - Weatherly, David; Sheehan, Nicholas; Kitchen, Rebecca (Collins, 2015)
Case studies in the book will include: samples of the breadth studies at Key Stage 3, key processes in both physical and human geography, integration of higher order thinking skills to exemplify that the world is a complex and interconnected place. Enquiry topics: 1. 'Middle' - of what? 'East' - of where? - Is the Middle East a region? -- 2. Issues in the ocean - Is our use of ocean resources sustainable? -- 3. Going boldly - Is India's space programme justified? -- 4. From Shangombo to South Tavy Head - Why are Thandi and Moses working in Soweto market? -- 5. Using someone else's water - How does water consumption create interdependence and conflict? -- 6. Biodiversity under threat - Can economic development on Borneo be sustainable?